The Advanced Throwers Ten Exercise Program: A new exercise series for enhanced dynamic shoulder control in the overhead throwing athlete - Wilk, K. E.; Yenchak, A. J.; Arrigo, C. A.; Andrews, J. R. (The Physician and Sportsmedicine, 2011)
The overhead throwing motion is a high-velocity, extremely stressful athletic movement. Its repetitive nature places tremendous demands on the entire body, frequently resulting in injury to the throwing shoulder. Such injuries, whether managed nonoperatively or surgically, require a multiphased approach beginning with exercises to restore muscular strength and proprioception, and advancing to more demanding exercises to improve power, endurance, and dynamic control. This article presents a new and innovative approach to the rehabilitation of the overhead throwing athlete, The Advanced Throwers Ten Exercise Program. This expanded program incorporates throwing motion-specific exercises and movement patterns performed in a discrete series, utilizing principles of coactivation, high-level neuromuscular control, dynamic stabilization, muscular facilitation, strength, endurance, and coordination, which all serve to restore muscle balance and symmetry in the overhead throwing athlete. This program is a continuation of the Throwers Ten Exercise Program, which has been utilized with excellent results in clinical practice and in athletic performance training. This unique combination of advanced exercise techniques bridges the gap between rehabilitation and training, facilitating a kinetic linking of the upper and lower extremities and providing a higher level of humeral head control necessary for the overhead throwing athlete`s symptom-free return to sports.